Measurement Properties of Canadian Agility and Movement Skill Assessment for Children Aged 9–12 Years Using Rasch Analysis - Chang, Jindong; Yong, Liming; Yan, Hai; Wang, Jibing; Song, Naiqing (Frontiers in Public Health, 2021)
The Canadian Agility and Movement Skill Assessment (CAMSA) was recently widely used to assess fundamental motor skills in children. Although the CAMSA is reported to be reliable and valid, its measurement properties are not clear. This study aimed to examine the measurement properties of the CAMSA in a sample of Chinese children using Rasch analysis. The study sample was from 1094 children aged 9-12 years in Zunyi City, Guizhou Province. Descriptive data were analyzed using SPSS 24.0 software, and the dichotomous data were analyzed by Winsteps version 4.5.4 and Facets 3.67.1 software performing Rasch analysis. The present study investigated CAMSA measurement characteristics by Rasch analysis, including the reliability of the rating instrument, unidimensionality, item-fit statistics, and differential item functioning (DIF). Inter-rater reliability and retest reliability showed that the CAMSA had a good internal consistency. Rasch analysis indicated that the CAMSA was unidimensional, locally independent, and had a good item-fit-statistic. Additionally, the CAMSA displayed a good fit for the item separation index (12.50 > 2.0), as well as for item reliability (0.99 > 0.90). However, the item difficulty of the CAMSA did not fit well with personal ability, and a significant DIF was found across genders. In the Chinese children sample test, the CAMSA demonstrated appropriate goodness-of-fit validity and rater reliability. Thus, future research will explore item difficulty and person ability fit, as well as DIF across genders.